Pengaruh Sponsorship terhadap Brand Awareness Livin’ by Mandiri (Studi pada Event E-Sport MPL ID Season 8) - Andy Gunawan; H. H. Daniel Tamburian (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Sponsorship is a type of marketing or advertising that, when done correctly, can be very effective. Livin' by Mandiri, a mobile banking product that is accessible and has a target market of young people who need practicality, is one of Bank Mandiri's newest products. The purpose of this study was to know if sponsorship at the MPL ID Season 8 event influenced Livin' by Mandiri's brand awareness. Sponsorship and Brand Awareness are the variables used in this study. In this study, sponsorship has three dimensions: target audience reach, compatibility with the company's or brand's positioning, and message capacity. In this study, brand awareness has four dimensions: Unaware of Brand, Brand Recognition, Brand Recall, and Top of Mind. This study used quantitative research methods, and the population studied in this research is the MPL ID Season 8 audience, which has an average viewership 447,142 viewers. The Slovin formula was used to find the number of samples needed in this research. The data in this study indicates that sponsorship at the MPL ID Season 8 event has an effect on Livin' by Mandiri brand awareness, there is a sufficient connection between sponsorship and brand awareness, and there is a strong influence between sponsorship and brand awareness. Sponsorship merupakan salah satu cara pemasaran atau periklanan yang sangat efektif jika dilakukan dengan tepat. Salah satu produk terbaru dari Bank Mandiri adalah Livin’ by Mandiri, produk mobile banking yang dapat diakses dan mempunyai target pasar anak-anak muda yang membutuhkan kepraktisan. Tujuan penelitian ini adalah untuk mengetahui apakah sponsorship pada event MPL ID Season 8 berpengaruh terhadap brand awareness Livin’ by Mandiri. Variabel pada penelitian ini adalah Sponsorship dan Brand awareness. dimensi sponsorship adalah Target Audience Reach, Compatibility with the Company’s or Brand’s Positioning & Message Capacity. Dimensi brand awareness yaitu Unaware of Brand, Brand Recognition, Brand Recall, Top of Mind. Peneliti menggunakan metode penelitian kuantitatif dan populasi penelitian ini adalah penonton MPL ID Season 8 yang mempunyai average viewers sebanyak 447,142 penonton. Untuk menentukan jumlah sampel yang dibutuhkan, peneliti menggunakan rumus Slovin. Hasil data pada penelitian ini menunjukkan bahwa terdapat pengaruh dari sponsorship pada event MPL ID Season 8 terhadap brand awareness Livin’ by Mandiri. Dari data penelitian ini, ditemukan bahwa terdapat hubungan yang cukup antara sponsorship dan brand awareness, dan terdapat pengaruh yang signifikan antara sponsorship dan brand awareness.